Reasons for low academic achievement among public school students from the point of view of mathematics teachers in the city of Aqaba - Al-Issa, Asma Ismail (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reasons for the low academic achievement of public school students from the point of view of mathematics teachers in the city of Aqaba. For data analysis, arithmetic means, standard deviations, t-test for independent samples, one-way analysis of variance, and (LSD) test were used. This is significant in terms of the arithmetic average, which amounted to (3.66), as it was found that the most important reasons for low achievement are the lack of incentives for the creative student, in addition to the fact that parents’ preoccupation with their children does not encourage education, and the weak financial return for the teacher, as well as the lack of incentives for the creative teacher, and based on the The results of the study The researcher made several recommendations, the most important of which were: the necessity for mathematics teachers to use incentives for students in basic schools in order to increase their academic achievement, and the need for mathematics teachers to follow appropriate methods in the education process in order to increase their academic achievement. The level of academic achievement.‏
Keywords: low academic achievement; public school students; mathematics teachers; Aqaba city